THE URGENCY OF THE CRIMINAL POLICY IN CRIME MITIGATION POLICE PROFESSION - Tahir, Ridwan (Tadulako University, 2016)
This article aims to reveal the characteristics of the crimes committed by the police in general, and then continued by asserting the main orientation of the criminal policy in crime prevention. Next, will be discussed more specifically about the urgency of the criminal policy in the prevention of the crimes committed by the police. This paper, presented using data and information from literature sources, then analyzed qualitatively with decomposition descriptive and prescriptive analytics. The focus of the discussion of this article will be directed to the issue of urgency criminal policy in relation to the role of agency compensation and rehabilitation for the abuses of power that are criminogen in the investigation process established through pretrial agencies that the results are only set compensation and rehabilitation as a result of misuse of the police profession. To that end, the weakness of the criminal law policy, need to be updated, ie, by adding the authority to institute pretrial may also recommend its findings to be prosecuted and criminal sanctions